ANTIMICROBIAL ACTIVITY OF ACACIA NILOTICA AGAINST SOME BACTERIAL ISOLATES ASSOCIATED WITH WOUND INFECTIONS - Jodi, S. M.; Umar, N.; Ungo-kore, H. Y.; Ngwai, Y. B. (FUDMA Journal of Sciences, 2022)
The search for biologically active compounds extracted from traditionally used plants is relevant due to the increasing resistance of bacteria to synthetic antibiotics and the occurrence of fatal opportunistic infections. Acacia nilotica, of the family leguminosae, is one of the oldest existing plant species having various therapeutic, biological and ethno-botanical claims and has diverse medicinal properties. This study was designed to determine the antimicrobial activity of leaf and stem-bark extract of Acacia nilotica against some bacterial isolates associated with wound infections. Leaf and stem-bark of Acacia nilotica plant was collected, identified, dried and extracted with 100% ethanol. The antimicrobial activity of the extracts and the fractions were evaluated against Staphylococcus aureus (SA), Bacillus subtilis (BS), Pseudomonas aeruginosa (PA) and Escherichia coli (EC) using agar well diffusion technique. Minimum inhibitory concentration (MIC) and Minimum bactericidal concentration (MBC) of the leaf and stem-bark extract was determined using microbroth dilution method. Phytochemical screening was carried out on the extracts and the leaf extract was subjected to liquid-liquid fractionation where n-hexane, ethyl acetate and residual aqueous fractions were obtained. The leaf and stem-bark extracts of Acacia nilotica were both active against the test organisms, but the leaf extract was more active. Antimicrobial activity against SA was the highest (at diameter zone of inhibition of 32.00Â±0.00 mm); and was observed in with the leaf extract. The MICs of the extracts against the organisms were 15.6-31.3 mg/ml (leaf) and 125 mg/ml (stem-bark); and the MBCs were 31.3 mg/ml (leaf) and 250 mg/ml (stem-bark). Tannins, flavonoids, phenols
Keywords: Acacia nilotica, Honey, Antifungal activity, Phytochemicals